CAUCHY PROBLEM OF PARABOLIC SYSTEM OF PSEUDODIFFERENTIAL EQUALIZATIONS WITH IMPULSIVE BY INFLUENCING - Лучко, Володимир Миколайович; Матійчук, Михайло Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The decision of task Cauchy is got for the parabolic pseudo differential system of equalizations with the impulsive influencing. Pseudo differential operators are interpreted as gipersingular integral operators. Communication between them is carried out by the image of elements of matrix character through spherical functions.